2006
DOI: 10.1002/erv.666
|View full text |Cite
|
Sign up to set email alerts
|

Discursive constructions of ‘eating disorders nursing’: an analysis of nurses' accounts of nursing eating disorder patients

Abstract: The contribution of nurses is a significant but notably underresearched aspect of hospital-based eating disorders treatment. This paper reports a qualitative interview-based study in which 15 nurses were interviewed about nursing children and adolescents diagnosed with eating disorder. A discourse analytic methodology was employed to analyse the resulting interview transcripts and focuses, in particular, on elucidating the various ways in which 'eating disorders nursing' was construed in participants' accounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
60
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 58 publications
1
60
0
Order By: Relevance
“…When nursing consumers with anorexia, non‐specific nurse initiated supportive measures are considered highly therapeutic (Ryan et al . ). The participants from this study found that strong relationships with nurses served a therapeutic purpose.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…When nursing consumers with anorexia, non‐specific nurse initiated supportive measures are considered highly therapeutic (Ryan et al . ). The participants from this study found that strong relationships with nurses served a therapeutic purpose.…”
Section: Discussionmentioning
confidence: 97%
“…Nursing methods, care approaches and strategies to deliver care (such as how a nurse might successfully encourage adherence to a meal plan) are under‐researched (Ryan et al . ). There are considerable discrepancies in approaches between healthcare providers in establishing negotiable and non‐negotiable treatment components (Geller & Srikameswaran ).…”
Section: Introductionmentioning
confidence: 97%
“…Discourse analytic research is ideally suited to meet this challenge: to analyse 'recovery' as socio-culturally located and to explicate the potentially diverse meanings that, for example, 'illness', 'self', 'treatment' and 'recovery' may hold (e.g. Gremillion, 2003;Malson, 1998;Malson, Finn, Treasure, Clarke, & Anderson, 2004;Ryan, Malson, Clarke, Anderson, & Kohn, 2006). The aim of this paper is therefore to build on these analyses, presenting a post-structuralist discourse analysis of the ways in which participants talked about their current and imagined future selves and the implications this has for understanding recovery from a more patient-centred perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are well-known ethical, practical and systemic problems treating people with eating disorders, there remain few qualitative studies of healthcare professionals' attitudes and experiences of eating disorders and their treatment. Previous qualitative studies have focussed specifically on the eating disorder, the patient or the therapeutic relationship (Hepworth, 1999;Jarman, Smith, & Walsh, 1997;King & Turner, 2000;Ramjan, 2004;Ryan Malson, Clarke, Anderson, & Kohn, 2006). Yet, there are wider issues that affect how eating disorders are treated, so this study set out to explore healthcare professionals' views of eating disorders and the services provided for them.…”
mentioning
confidence: 99%